Direct Distribution of Resource Revenues : Worth Considering? - Gupta, Sanjeev (Staff Discussion Notes; Staff Discussion Notes, 2014)
Some scholars have argued that direct distribution of natural resource revenues to the population would help resource-rich countries escape the 'resource curse.' This discussion note analyzes whether this proposal is a viable policy alternative for resource-rich countries. The first priority for policymakers is to establish fiscal policy objectives to support macroeconomic stability and development objectives. In this regard, the establishment of an adequate fiscal framework that informs decisions on how much to save and invest, or how to smooth out revenue volatility, and deal with exhaustibility issues should precede any discussion of direct distribution of resource wealth to the population.